Nursing of a patient undergoing transcatheter aortic valve implantation for aortic valve stenosis and lower limb artery occlusion (1例主动脉瓣狭窄合并下肢动脉闭塞患者经导管主动脉瓣置换术的护理) - SI Shanshan (斯珊珊) (Association of Integrative Nursing, 2023)
To summarize the perioperative nursing methods of an elderly patient with aortic stenosis complicated with lower limb artery occlusion. Based on the establishment of nurse-led multidisciplinary team as a comprehensive nursing intervention chain, efforts were made to enhance the management of heart failure, hemodialysis management, gangrene wound nursing, complications observation and psychological nursing for the patient. After 75 days of careful treatment and nursing, the patient's condition was stable and discharged from hospital successfully. The establishment of MDT nursing team in the perioperative period and the implementation of perioperative comprehensive interventions are beneficial to the early recovery of the patient. (探讨主动脉瓣狭窄合并下肢动脉闭塞的老年患者的围手术期护理方法。通过建立以护士为主导的多学科团队(MDT)协作小组为综合护理干预链, 围绕心力衰竭管理、血透管理、坏疽创面护理、并发症观察、心理护理5个方面对患者积极干预。经过75 d的精心治疗和护理, 患者病情稳定出院。在老年患者围手术期组建MDT护理团队, 实施围手术期综合干预, 旨在促进患者早期康复, 减少术后并发症。)